Epidemiology and demography of Chronic Kidney Disease in Pakistan- A review of Pakistani literature - Imtiaz, Salman; Alam, Ashar (Pakistan Journal of Kidney Diseases, 2023)
Background: CKD is spreading like an epidemic. There is a dire need to understand the true prevalence as well as the causes of CKD in both urban and rural areas of Pakistan in relevance to age and gender. In this background, there is a need to know what has been done so far to understand the status of CKD in Pakistan. Materials and Methods: We selected the articles published through PubMed and Google scholar and the following keyword were used, epidemiology, demography, prevalence, chronic kidney disease, chronic renal insufficiency, etiology, and causes of CKD, Pakistan. We found four articles that evaluated the prevalence and five articles that dealt with the causes of CKD. We included all articles in our analysis. Results: The overall prevalence among all age groups was found to be 21.2%. The highest CKD prevalence was reported as 29.9% and the lowest at 12.5%. The highest prevalence was found in patients more than 50 years of age (43.6%). Two studies showed male predominance (62% and 54.4%), while two showed a female majority (64%,52%). The most common cause of CKD was found to be Diabetic nephropathy (27.1%), followed by CKD of unknown etiology (16.6%) and renal stone disease (12.4%) Conclusion: The prevalence of CKD is high, especially in the older population. Similarly, the leading causes of CKD are also different in all studies due to center dependence, hospital-specific and urban locations. DM, CKDu, and renal stone disease are common causes of CKD Keywords: Pakistan, chronic kidney disease, prevalence, epidemiology,